Bifurcation Analysis and Electronic Circuit for Sprott Jerk System - R Apip Miptahudin (International Journal of Quantitative Research and Modeling, 2021)
In this paper, the Sprott jerk system based quadratic function is presented. The dynamics of this system is revealed through equilibrium analysis, phase portrait, bifurcation diagram and Lyapunov exponents. The Sprott system can exhibit a chaotic attractor, which has complex dynamic behavior. Finally, the circuit implementation is carried out to verify the Sprott Jerk system.  The comparison between the MATLAB and MultiSIM simulation results demonstrate the effectiveness of the Sprott system.